The Ulva flexuosa complex (Ulvaceae, Chlorophyta): an updated identification key with special reference to the freshwater and hyperhaline taxa - Rybak, Andrzej S. (Phytotaxa, 2018)
The paper presents an updated version of the phycological key which includes additional morphological features, so as to facilitate identification of taxa (subspecies and variants) from the Ulva flexuosa complex, spanning populations from ecosystems with varying degrees of salinity. Data were collected in several locations in central and western regions of Poland. Only two subspecies were observed in inland water ecosystems: U. flexuosa subsp. pilifera, and subsp. paradoxa. Another taxon—U. flexuosa subsp. flexuosa, inhabits only brackish waters of costal lakes and estuaries. Two further taxa, namely U. flexuosa var. linziformis and subsp. biflagellata are found only in marine ecosystems and do not tend to settle in freshwater habitats.